Monitoring and strengthening of existing facilities in the neighbourhood of in-fill building = Monitorowanie i wzmacnianie obiektów istniejących w sąsiedztwie budowy plombowej - Runkiewicz, Leonard; Sieczkowski, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper focuses on the following issues: technical issues regarding the construction of infill buildings and their influence on the old neighbouring buildings, analysis of the dangers, damages and catastrophes of old traditional buildings, rules regarding monitoring of the technical conditions of existing old buildings, settlements of the ground and their influence on the neighbouring buildings, examples of the ground settlements observed during construction of infill buildings in Warsaw, examples of strengthenings realized near brick buildings and listed buildings.
Keywords: budynki; głębokie wykopy; budownictwo plombowe; monitorowanie obiektów; wzmacnianie obiektów; buildings; deep excavations; infill building; monitoring; strengthenings